Effect of Ion Nitriding on Gear Accuracy - Quan Yuyun (Jixie chuandong)
Nitriding is widely used in the surface strengthening of gears, but there is a lack of research on the distortion and accuracy of gears after nitriding. Thus, the reasons of nitriding distortion are analyzed and the distortion factors and general laws are explained. The gears made of 42CrMo and 40CrNiNo with three specifications are treated by deep ion nitriding, and the changes of various errors before and after nitriding are systematically measured; the test shows that accuracy of the gears after nitriding decreases by 0.5-1 grade. The influence laws of deep ion nitriding on gear distortion and the trend of gear accuracy decreases are obtained, which provides reference for the design and manufacturing of nitriding gears and control of distortion.